2020
DOI: 10.1007/s43452-020-00118-x
|View full text |Cite
|
Sign up to set email alerts
|

Seismic behaviour of cross-shaped steel fibre reinforced concrete columns

Abstract: This paper proposes a novel cross-shaped column in which steel fibre reinforced concrete (SFRC) is integrated with a highstrength stirrup to enhance its seismic behaviour. An experimental investigation was conducted on eight cross-shaped column specimens subjected to cyclic lateral loading. All of the specimens were evaluated in terms of their cracking patterns, failure modes, hysteresis behaviour, deformation and ductility, strength and stiffness degradation, and energy dissipation performance. The effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Due to the shortcomings of self-weight and low tensile strength of concrete, many scholars have made up for these shortcomings by adding various fibers [20][21][22]. Jianqiang Wei et al [23] found that when the substitution rate of rice husk ash was 30%, the alkaline degradation and mineralization of sisal fiber in cement matrix were alleviated most effectively, which ensured that sisal fiber-made green natural fiber-reinforced cement composites have better tensile properties and durability.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the shortcomings of self-weight and low tensile strength of concrete, many scholars have made up for these shortcomings by adding various fibers [20][21][22]. Jianqiang Wei et al [23] found that when the substitution rate of rice husk ash was 30%, the alkaline degradation and mineralization of sisal fiber in cement matrix were alleviated most effectively, which ensured that sisal fiber-made green natural fiber-reinforced cement composites have better tensile properties and durability.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the properties were greatly influenced by the aspect ratio [22,23], tensile strength [23], shape [24][25][26][27], and volume content [28][29][30] of steel fibers, and the shape and volume content are the two most frequently studied factors. Generally, the strength of RPC or UHPC improves gradually with the increase of steel fiber content [31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%